2004
DOI: 10.1074/jbc.m402820200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neuronal Voltage-gated Sodium Channels by the Ubiquitin-Protein Ligases Nedd4 and Nedd4-2

Abstract: Nedd4 and Nedd4-2 are ubiquitin-protein ligases known to regulate a number of membrane proteins including receptors and ion transporters. Regulation of the epithelial Na ؉ channel by Nedd4 and Nedd4-2 is mediated via interactions between the PY motifs of the epithelial sodium channel subunits and the Nedd4/Nedd4-2 WW domains. This example serves as a model for the regulation of other PY motif-containing ion channels by Nedd4 and Nedd4-2. We found that the carboxyl termini of the six voltage-gated Na ؉ (Na v ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 20 publications
10
141
1
Order By: Relevance
“…In fact, Nedd-4 and FGF14-1A decreased the current density of Na v 1.1-R1916G but had no effect on the wild type, consistently with published data (Fotia et al, 2004;Lou et al, 2005;Rougier et al, 2005). Thus, the effects of R1916G depend on the contrasting action of rescuing and downregulating interactions.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In fact, Nedd-4 and FGF14-1A decreased the current density of Na v 1.1-R1916G but had no effect on the wild type, consistently with published data (Fotia et al, 2004;Lou et al, 2005;Rougier et al, 2005). Thus, the effects of R1916G depend on the contrasting action of rescuing and downregulating interactions.…”
Section: Discussionsupporting
confidence: 76%
“…The interaction with voltage gated Na + channel α subunits in general increases the internalization of the channel and possibly its degradation, but Nedd4-1 can interact with some Na + channel α subunits inducing just a moderate downregulation, or no downregulation at all (Fotia et al, 2004;Rougier et al, 2005). Na v 1.1 contains a conserved PY motif in the C-terminal cytoplasmic domain, downstream of R1916G (Fig.…”
Section: Effects Of Other Interacting Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Na v 1.7 is essential for pain sensation, NEDD4-2 downregulation of Na v 1.7 in mammalian cells was investigated, as previously reported in Xenopus oocytes (24). Whole-cell Na + currents (I Na ) were recorded in HEK293 cells cotransfected with Na v 1.7 and NEDD4-2.…”
Section: Peripheral Nerve Injury Reduces Nedd4-2 Expression In Drgmentioning
confidence: 99%
“…All Na v isoforms, except Na v 1.4 and Na v 1.9, possess a PY motif and are potential targets of NEDD4-2. In vitro experiments have indicated that NEDD4-2 can negatively regulate the epithelial sodium channel ENaC (22) and Na v s (23,24). The functional relevance of NEDD4-2 in sensory neurons, as well as its possible involvement in pain sensitivity, have yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%